2020
DOI: 10.3332/ecancer.2020.1043
|View full text |Cite
|
Sign up to set email alerts
|

Cervical carcinoma in the setting of uterovaginal prolapse: comparing standard versus tailored management

Abstract: Objectives: Cervical cancer in the setting of uterovaginal prolapse is exceedingly rare. Altered anatomy can complicate treatment of underlying cancer. We first present a rare case of cervical cancer with invasion of uterovaginal prolapse as well as a systematic review of similar reported cases in the literature. The objective of this study was to compare the practice patterns and outcomes regarding cervical cancer with invasion of procidentia. Methods:We conducted a systematic search of online databases (PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The low survival rate of patients with advanced stage of vaginal cancer is attributed to the lack of effective treatment for this category of patients in our setting. Thus, given the limited options for patients with recurrent and metastatic cervical cancer, which is similar in nature to vaginal cancer, Kahn et al [19] recommend considering the possibility of immunotherapy with pembrolizumab in PD-L1-positive patients. Few studies have examined the role of residence in diagnosis and treatment outcomes in patients with cervical cancer, which is the closest in aetiology to vaginal cancer and other cancers [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The low survival rate of patients with advanced stage of vaginal cancer is attributed to the lack of effective treatment for this category of patients in our setting. Thus, given the limited options for patients with recurrent and metastatic cervical cancer, which is similar in nature to vaginal cancer, Kahn et al [19] recommend considering the possibility of immunotherapy with pembrolizumab in PD-L1-positive patients. Few studies have examined the role of residence in diagnosis and treatment outcomes in patients with cervical cancer, which is the closest in aetiology to vaginal cancer and other cancers [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the prolapse facilitated the radiotherapy treatment and minimized the risk of visceral injury due to radiation. Although in most cases reported vaginal hysterectomy with bilateral iliopelvic lymphadenectomy has been performed prior to additional treatment, a more conservative approach might be beneficial in cases of severe comorbidity similar to our patient [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for cervical cancer in the setting of a uterine prolapse varies widely across literature. Most reported cases suggest acceptable clinical and functional outcomes with a radical vaginal hysterectomy with bilateral pelvic lymphadenectomy followed by adjuvant chemoradiation ( Kahn et al, 2020 ). Matsuo et al reported potentially better outcomes following surgery-based treatment with a 5-year survival of 77% compared to 68% in patients receiving RT alone ( Matsuo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the peak incidence of symptomatic POP occurs between ages 70 and 79 years ( Barber and Maher, 2013 ). A review by Kahn et al identified 15 cases of cervical cancer with uterine prolapse between 1990 and 2017, 14 of which had squamous cell carcinoma (SCC) and 1 had clear cell adenocarcinoma ( Kahn et al, 2020 ). The mean age was 74 years (range 54–89), reflecting the typical age predilection of POP.…”
Section: Introductionmentioning
confidence: 99%